Ver-Based Evidential Re/Positioning Strategies in Conservative Digital Newspaper Readers’ Comments on Controversial Immigration Policies in Spanish - Elena Domínguez Romero (Languages, 2023)
The emergence of political polarization in Europe has intensified divisions among citizens regarding immigration, inequality, and racism. The present paper investigates the use of ver-based (“see”-based) evidentiality in positioning and repositioning strategies by conservative Spanish readers of the digital newspapers ABC and La Razón. The study focuses on their responses to two different controversial measures involving immigrants and refugees taken in by the Spanish government. Such measures relate to the Aquarius (2018) and the Open Arms (2019) incidents. The analysis will be corpus, content-based, and grounded in positioning theory and theories of visual evidential perception. The ultimate aim is to explore the instances of ver-based evidentiality introducing positioning and repositioning strategies that are present in the corpus. Subsequently, we will classify and analyze the viewpoints expressed by conservative readers through these ver-based evidential markers.